GENETIC VARIABILITY FOR GRAIN NUTRIENTS CONTENT IN COASTAL RICE COLLECTIONS OF BANGLADESH - Shahrin, F; Roy, P; Raihan, M S; Haque, M M; Rasul, M G (International Journal of Research -GRANTHAALAYAH, 2021)
Overcoming malnutrition through biofortification breeding in rice is aimed to assist nutritional food security in Bangladesh. So to select parents for nutritional improvement, estimation and exploitation of mineral nutrients reserves of rice grain and their variability assessment in different genotypes is essential. Eighty-five (85) T. aman rice genotypes collected from different coastal regions of Bangladesh were evaluated at the Advanced Plant Breeding laboratory, GPB of BSMRAU to estimate the grain nutrients content and to elucidate their genetic variability among the genotypes. Considerable significant variation (0.1% level of probability) was noted among the genotypes for studied different grain nutrient contents and yield per hill. The mean values of N, P, K, Ca, Mg, Na, Zn, Fe, Cu, Mn and grain yield/ hill were 10788.24 mg/kg, 804.85 mg/kg, 3798.58 mg/kg, 13795.29 mg/kg, 2778.87 mg/kg, 3771.17 mg/kg, 7.25 mg/kg, 5.01 mg/kg, 1.05 mg/kg, 1.90 mg/kg and 433.29 g, respectively. Box and whisker plots analysis were done to represent data graphically for better understanding. Histogram was used to present the frequency distribution of genotypes for N, P, K, Ca, Mg, Na, Zn, Fe, Cu, Mg and Grain yield/hill content in 85 diverged rice genotypes All the traits had equality in genotypic and phenotypic variances with high heritability and high genetic advance which indicated preponderance of additive gene effects for these traits. The genotype R080 (Chinigura) contained the highest content of grain P, Fe and Cu. The R030 (Mota Dhan), R040 (Dudh Kalam) and R019 (Chikon Dhan) were noted for the highest Ca, Mg and Na content, respectively. The maximum N and Zn content were observed in R029 (Dudh Kolom) and R075 (Gopal Bogh), respectively. R083 (Lal Dhan) was marked for the highest grain yield/ hill and K content. Genetic variability parameters, heat map analysis and neighbor joining clustering methods indicated these genotypes including R079 can be considered for biofortification program and used as parents for the improvement of those grain nutrients in rice breeding.